Shaivism’s Ontological and Social Vision: Readings from the Vaisesika Sutra and Tantric Texts (Sahayaatra सहयात्रा, 2025)
This article examines Shaivism’s ontological and social vision through a critical engagement with the Vaisesika Sutra and Tantric texts, focusing on how classical materialistic principles are interpreted within Shaiva philosophy to articulate a dynamic and cohesive understanding of the world and society. The Vaisesika Sutra, known for its materialistic framework that categorizes reality into dravya(substances), guna (knowledge and skill), and karma(actions), emphasizes the natural laws governing the universe. While it presents an objective and law-bound order, Shaivism interprets these laws as being established and sustained by Shiva, the ultimate divine principle who is the maker and regulator of natural order. This Shaiva interpretation transforms apparent tensions—such as between the permanence of substance and the flux of action—into a dynamic dialectic where contradiction becomes a fundamental force driving change and transformation. By sacralizing natural law as an expression of Shiva’s will, Shaivism presents the world as a unified, living reality infused with divine presence.Tantric texts extend this vision by framing social order and justice as expressions of cosmic balance, where conflict and opposition coexist in dynamic harmony upheld by Shiva and his Shakti (power). This conception suggests that social tensions and contradictions are not to be suppressed but embraced as creative impulses that sustain renewal and harmony. Drawing from this philosophical foundation, the article explores the potential application of Shaiva thought to the contemporary quest for a just and inclusive society in Nepal—a society where diversity, social justice, and unity emerge from the dynamic interplay of differences rather than enforced uniformity. Shaivism’s vision offers a paradigm that embraces complexity and contradiction as sources of social cohesion and ethical governance, thereby contributing a rich philosophical resource for addressing Nepal’s pluralistic social challenges.